The Integration of Learning Outcomes and Graduate Attributes in the Australian Higher Education Sector. Part I: Integration, Evidence and Legal Consequences - Do, Christina; Smith, Leigh (2021)
Australian Commonwealth-funded reports and academic literature suggest that it is difficult for universities to produce convincing evidence that the institutions have comprehensively and systematically developed the learning outcomes and graduate attributes promoted in their educational policy. While the higher education sector has reported numerous successful curriculum mapping approaches since 2011, specifically focused on the development of course learning outcomes and graduate attributes, an ongoing concern for the sector is the difficulty of providing conclusive evidence demonstrating graduate achievement of the outcomes and the standard of the achievement. This two-part series considers the integration of learning outcomes and graduate attributes from a legal perspective. Part I discusses the difficulties associated with the implementation of learning outcomes and graduate attributes, and the potential legal consequences that universities may face from affected stakeholders, if providers are unable to produce persuasive evidence demonstrating the integration of the learning outcomes and graduate attributes. Part II outlines measures universities can implement to mitigate their potential legal liability. Although the formation and integration of learning outcomes and graduate attributes is an important issue in higher education internationally, the focus of this paper will be on the higher education sector within Australia.